Brachytherapy in non melanoma skin cancer of eyelid: a systematic review - Frakulli, Rezarta; Galuppi, Andrea; Cammelli, Silvia; Macchia, Gabriella; Cima, Simona; Gambacorta, Maria A.; Cafaro, Ines; Tagliaferri, Luca; Perrucci, Elisabetta; Buwenge, Milly; Frezza, Giovanni; Valentini, Vincenzo; et al. (Journal of Contemporary Brachytherapy, 2015)
Purpose: Non melanoma skin cancers (NMSC) of eyelid are uncommon. Many treatments approach are available with surgery being considered as the gold standard. Radiotherapy is an effective alternative in patients unfit for surgery. Brachytherapy (BT) might be a better therapeutic option due high radiation dose concentration to the tumor and rapid dose fall-off resulting in normal tissues sparing. The aim of this review is to evaluate local control, toxicity, and functional cosmetic outcome of BT in NMSC of eyelid. Material and methods: A systematic search of the bibliographic databases PubMed, Scopus, and Cochrane Library from the earliest possible date through October 2015 was performed. Only studies published in English were included. Results : Six articles fulfilled the selection criteria and were included in our review. Due to high risk of bias, all studies were classified to provide a low level of evidence (according to Scottish Intercollegiate Guidelines Network Classification). No randomized controlled trials or case control studies were founded. Brachytherapy was well tolerated with acceptable toxicity and high local control rates (median: 95.2%). Functional and cosmetic outcome were reported in five study as acceptable good functional-cosmetic outcome (median: 100%). Conclusions : To date, few evidences are available on the role of BT in eyelid NMSC, and they show satisfactory results in terms of local control and functional cosmetic outcome. Therefore, prospective controlled trials are justified.